Isolation and characterization of SARS-CoV-2 Beta variant from UAE travelers. Issue 2 (February 2022) - Yadav, Pragya D.; Sarkale, Prasad; Razdan, Alpana; Gupta, Nivedita; Nyayanit, Dimpal A.; Sahay, Rima R.; Potdar, Varsha; Patil, Deepak Y.; Baradkar, Shreekant; Kumar, Abhinendra; Aggarwal, Neeraj; Shete, Anita M.; et al.
Highlights: Emergence of SARS-CoV-2 variant has been serious threat to public health. Travel is an important factor in spread of these variants across the globe. We have isolated VOC Beta variant from UAE travelers. Sequence of isolates had 99.88–99.96% nucleotide identity with Beta variant. Abstract: Background: The emergence of SARS-CoV-2 variants in places where the virus is uncontained poses a global threat from the perspective of public health and vaccine efficacy. Travel has been important factor for the easy spread of SARS-CoV-2 variants worldwide. India has also observed the importation of SARS-CoV-2 variants through international travelers. Methods: In this study, we have collected the oropharyngeal and nasopharyngeal swab specimens from 58 individuals with travel history from United Arab Emirates (UAE), East, West and South Africa, Qatar, Ukraine and Saudi Arabia arrived in India during February–March 2021. The clinical specimens were initially screened for SARS-CoV-2 using Real time RT-PCR. All the specimens were inoculated on to Vero CCL-81 cells for virus isolation. The viral isolates were further sequenced using Next-Generation Sequencing. Results: All 58 cases were tested positive for SARS-CoV-2 using Real time RT-PCR. Four specimens showed progressive infectivity with fusion of the infected cells with neighboring cells leading to large mass of cells. Replication competent virus was confirmed from culture supernatant of the passage 2 using Real time RT-PCR. Two plaque purified SARS-CoV-2 isolates demonstrated high viral RNA load of 3.8–7.5 × 10 11 and 1.1–1.6 × 10 11 at passage 4 and 5 respectively. Nucleotide variations along with amino acid changes were also observed among these two isolates at passage 2–5. All four cases were male with no symptoms and co-morbidity. The sequence analysis has shown two different clusters, first cluster with nucleotide deletions in the ORF1ab and the spike, while second cluster with deletions in spike region. The viral isolates demonstrated 99.88–99.96% nucleotide identity with the representative sequences of Beta variant (B.1.351). Conclusion: These findings suggest easier transmission of SARS-CoV-2 variants with human mobility through international travel. The isolated Beta variant would be useful to determine the protective efficacy of the currently available and upcoming COVID-19 vaccines in India.